Asset classification, subsequent measurement and impairment testing for carbon emission trading - Tharatee Mookdee; Sheila Bellamy (European Financial and Accounting Journal, 2017)
With global efforts to combat climate change, accountants from participating entities worldwide need to report the economic value of carbon credits and related assets in carbon markets. However, the absence of formal accounting guidelines allows the selection of accounting practices and reporting methods based on individual judgment. Also, emitters are allowed to invest in carbon credit projects and trading. These circumstances have led to diversity in global accounting practices. As accounting is an international business language in a global business world, it is important to study emerging accounting practices for carbon emission trading. The main aim of this study is, therefore, to explore the accounting practices (asset classification, subsequent measurement and impairment testing) of carbon credit providers/traders. Sample companies from Australian mandatory and voluntary carbon markets were selected. The study was conducted using case-study methodology and in-depth interviews, supported by archival and secondary data. It was found that the preferred asset classification of carbon credits varies among case-site participants, according to specific market requirements and economic uncertainty. Valuation methods differ across sites due to internal operations and economic factors. Impairment testing requires reference price indices determined by the nature of assets and professionals.
Keywords: M41; 650; Accounting standards; Emission rights; Emission trading; EU ETS; Financial Accounting